Orientation of non-spherical protonated water clusters revealed by infrared absorption dichroism - Jan O. Daldrop (Nature Portfolio, 2018)
Protein-bound water clusters play a key role for proton transport and storage in molecular biology. Here, the authors show by simulations and experiments that the orientation of non-spherical protonated water clusters in bacteriorhodopsin is unveiled by polarization-resolved infrared spectroscopy.